(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-72-82 The relevance of this article lies in the priority of communicative pragmatics, in the development of such a new integral research area as psychoparemiology, in the interest of researchers in comforting and in the need to study the pragmatic potential of proverbs that can realize the intention of comforting in application to Germanic languages. The purpose of this work is to classify the proverbs of the English and German languages in accordance with the goals of comforting they realize and the ways to achieve these goals. Five groups of proverbs can be singled out by means of pragmalinguistic analysis. Proverbs of the first group can be used to change the negative attitude of the comforted person towards the situation to a positive one. They point out positive aspects of the situation or the possibility to benefit from it, minimize the problem, ask the comforted to be content with what is available to them. Proverbs of the second group assure that everything that happens is destined and claim that human hardships are inevitable, while joys are finite. They can also point out the impossibility to change past events. Proverbs of the third group make the comforted person gather strength, indicating positive effects of trials and challenges. They also instill hope that challenges can be overcome and the situation can change for the better. The fourth group aims at influencing the comforted person’s emotions by stating that distress is harmful and will be alleviated over time. Proverbs of the fifth group justify the actions of the interlocutor by claiming that mistakes can help a person gain important experience, they are in the human nature and inevitable and are not so bad compared to more damaging actions. Key words: communicative pragmatics, psychoparemiology, dialogue, comforting, proverbs